PKA-mediated phosphorylation of CREB and NMDA receptor 2B in the hippocampus of offspring rats is involved in transmission of mental disorders across a generation. (October 2019) - Huang, Yuejun; Hu, Liu; Li, Hui; Huang, Yanhong; Li, Yuewa; Yang, Jianhui; Gu, Jiajie; Xu, Hongwu
Highlights: Stress before pregnancy increases behavioral disorder of offspring in adolescence. Behavior of adolescent offspring may relate to PKA-CREB-NR2B in the hippocampus. Mental conditions may be across generations. Mental condition of female before pregnancy should be attention. Abstract: This study is aimed at the mechanism of transmission of mental disorders across a generation. We used 10 different stressors to establish an animal model of chronic unpredictable stress (CUS) before pregnancy. Forced swimming test (FST) and open field test (OFT) were used to analyze the behavior of 30-day-old adolescent offspring rats born to stress mothers. Magnetic resonance spectroscopy was used to measure glutamate, gamma-aminobutyric acid (GABA), and glutamine. Phosphate-activated glutaminase (PAG), glutamate decarboxylase (GAD), GABA-transaminase (GABA-T), protein kinase A (PKA), cAMP response element-binding protein (CREB), and N-methyl-D-aspartate (NMDA) receptor 2B (NR2B) were detected by western blot. Adolescent offspring rats in the CUS group exhibited depressive-like behavior in the FST and anxious behavior in the OFT. GAD was increased and GABA-T was decreased, which resulted in an increase in GABA levels and decrease of the glutamate/GABA ratio in the hippocampus of CUS offspring rats. Disruption of the glutamate/GABA–glutamine cycle was related to decrease PKA-mediated phosphorylation of CREB and NR2B in the hippocampus. These findings highlight the importance of mental health of females before pregnancy and suggest that CUS before pregnancy reduces p-CREB and p-NR2B in the offspring hippocampus, which could be responsible for behavioral disorders in the adolescent offspring.